Summation identities for representation of certain real numbers - George Grossman; Akalu Tefera; Aklilu Zeleke (International Journal of Mathematics and Mathematical Sciences)
We present identities used to represent real numbers of the form xum±yvn for appropriately chosen real numbers x, y, u, v and nonnegative integers m and n. We present the proofs of the identities by applying Zeilberger's algorithm.